2006
DOI: 10.2174/092986706775197881
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Chemistry of N-Acylhydrazones: New Lead-Compounds of Analgesic, Antiinflammatory and Antithrombotic Drugs

Abstract: In this article we provide an overview on the medicinal chemistry of new bioactive N-acylhydrazone (NAH) derivatives designed through the structural optimization of N-arylhydrazone precursors, originally planned by molecular hybridization of two known 5-lipoxygenase inhibitors, i.e. CBS-1108 and BW-755c. The analgesic, antiedematogenic and platelet anti-aggregating profile of several isosteric NAH compounds was investigated by using classical in vivo and ex-vivo pharmacological assays, which allowed the identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(48 citation statements)
references
References 29 publications
0
46
0
2
Order By: Relevance
“…In the case of acid hydrazides 1b and 1c, the reactions with benzaldehyde, adamantan-2-one, and cyclohexanone, respectively, in MeOH occurred smoothly at room temperature and yielded the expected hydrazones 8a-8f in high yields. The analogous reactions with 3 ) For some recent articles on synthesis and biological interest of acylhydrazones see [7a][8a] [13]. acetophenone required acid catalysis (AcOH in EtOH, reflux) to give 8e and 8f (Scheme 5), whereas with benzophenone no hydrazone was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of acid hydrazides 1b and 1c, the reactions with benzaldehyde, adamantan-2-one, and cyclohexanone, respectively, in MeOH occurred smoothly at room temperature and yielded the expected hydrazones 8a-8f in high yields. The analogous reactions with 3 ) For some recent articles on synthesis and biological interest of acylhydrazones see [7a][8a] [13]. acetophenone required acid catalysis (AcOH in EtOH, reflux) to give 8e and 8f (Scheme 5), whereas with benzophenone no hydrazone was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have indicated that the N-acylhydrazone subunit is a pharmacophore group with analgesic, anti-inflammatory, and antiplatelet properties (11). Therefore, we hypothesized that the compound LASSBio-788 may exert beneficial effects on atherosclerosis, which is a disease that closely associates with inflammation in the cardiovascular system.…”
Section: Anti-atherogenic Effects Of a New Thienylacylhydrazone Derivmentioning
confidence: 99%
“…The NAH subunit has been described as the pharmacophoric framework of several bioactive substances from different therapeutic classes 12,13 , indicating the privileged status of this moiety, as has been recently reviewed 14 . So, in the scope of a research program aiming to design, synthesize, and perform the pharmacological evaluation of new platelet antiaggregating lead-compound candidates, we developed new functionalized furyl 1,3-benzodioxolyl-N-acylhydrazone derivatives 9 (Figure 2), designed as isosteres of the antiplatelet thienyl-NAH derivatives 7 and 8.…”
Section: Introductionmentioning
confidence: 95%